TALENT RETENTION IN PRIVATE ENGINEERING INSTITUTIONS IN RURAL PARTS OF ANDHRA PRADESH, INDIA - Rao, Appari Gouri Sankar; Krishnan, Dr. A.R. (The journal of contemporary issues in business and government, 2023)
It has been observed that, Talent Retention in Higher Educational Institutions is an ongoing problem in rural parts of India and Andhra Pradesh is no exception to this phenomenon. Many private higher educational institutions especially Engineering Educational Institutions in rural Andhra Pradesh are on the wedge of closure and are not in a position to sustain due to lack of revenue generation to meet even the operational expenses and with this, the existing huge and expensive infrastructure of these sick institutions are going to turn in to National Waste. This has been the burning problem for the last six to seven years due to little importance given to the most important aspect, “Talent Retention”. It is strongly believed that, institutions are made up of staff both Teaching and Non-Teaching: Teaching Staff creating value through proven teaching & Learning processes, innovation, mentorship and many other relevant activities and Non-Teaching staff providing administrative and logistic support to fulfill the needs of the deliverables of Teaching staff. As, an Educational institution strives to meet its organizational goals, it must make sure that it has a continuous and integrated process for Recruiting, Training, Managing, Supporting and Compensating these people to achieve high success rate of Talent Retention.